2016
DOI: 10.3109/02770903.2015.1135946
|View full text |Cite
|
Sign up to set email alerts
|

Asthma management in New York City schools: A classroom teacher perspective

Abstract: Objective Classroom teachers play an important role in facilitating asthma management in school but little is known about their perspectives around asthma management. We examined the perspectives of classroom teachers around barriers to school asthma management. Methods We conducted key informant interviews with 21 inner-city classroom teachers from 3rd to 5th grades in 10 Bronx, New York elementary schools. Sampling continued until thematic saturation was reached. Interviews were recorded, transcribed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
(33 reference statements)
4
16
1
Order By: Relevance
“…Without formal asthma training for the school staff, it is surprising that the majority of principals believed that the teachers feel confident handling an asthma attack in the classroom. This claim was in contrast to the findings of our prior study where we observed that the majority of teachers felt unprepared in case of an emergency (Cain & Reznik, 2016). This discrepancy could stem from the principal’s interest in presenting the preparedness of the school staff in the best light and their lack of direct involvement in asthma care of the schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Without formal asthma training for the school staff, it is surprising that the majority of principals believed that the teachers feel confident handling an asthma attack in the classroom. This claim was in contrast to the findings of our prior study where we observed that the majority of teachers felt unprepared in case of an emergency (Cain & Reznik, 2016). This discrepancy could stem from the principal’s interest in presenting the preparedness of the school staff in the best light and their lack of direct involvement in asthma care of the schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
“…Rather, the reported “procedures” are loosely based on past experiences. This finding is consistent with our prior study, in which only one third of the interviewed teachers reported having a written policy in their school (Cain & Reznik, 2016). In this study, we found that often the schools mistakenly used administrative mechanisms, such as the MAFs, as a de facto “policy.” Even though the law mandates that children with chronic illnesses need to be accommodated by public schools under Section 504 of The Rehabilitation Act, the NYC Board of Education still lacks formal policies on asthma management.…”
Section: Discussionsupporting
confidence: 93%
“…the potential for a rapid decline in a child with asthma symptoms). Asthma education interventions have shown some promise in advancing teacher knowledge (Kawatha & Tawalbeh, 2015) yet several barriers exist including ineffective communication across school staff and inadequate access to asthma medications (Cain & Resnick, 2016; Hanley Nadeau & Toronto, 2016). Additionally, participating parents expressed frustration with school-based indoor exposures needing remediation; however, schools in low-income communities may not have resources to adequately remove mold and other triggers.…”
Section: Discussionmentioning
confidence: 99%
“…The level of awareness should be raised by training programs to meet the needs of children and to decrease school absenteeism. [1415161718]…”
Section: Introductionmentioning
confidence: 99%